2021
DOI: 10.1038/s43246-021-00222-2
|View full text |Cite
|
Sign up to set email alerts
|

Creation of stable water-free antibody based protein liquids

Abstract: Antibodies represent highly specific and high binding affinity biomolecular recognition elements for diagnostic assays, biosensors, and therapeutics, but are sensitive to denaturation and degradation. Consequently, the combination of existing in a hydrated state with a large and complex biomolecular structure results in loss of antibody-antigen binding, limited shelf-life, and decreased sensor response over time and under non-optimal conditions. The development and use of water-free protein liquids has led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…5 However, at the same time, water is highly labile to hydrolysis and oxidation, thus destabilizing protein's structure and function at elevated temperatures. 6 Therefore, there is a crucial need to find novel excipients and/or biocompatible solvents that could stabilize proteins and enhance their storage capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, at the same time, water is highly labile to hydrolysis and oxidation, thus destabilizing protein's structure and function at elevated temperatures. 6 Therefore, there is a crucial need to find novel excipients and/or biocompatible solvents that could stabilize proteins and enhance their storage capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…150 Overall, this is an innovative approach to overcome the limitations of the robustness of proteins to get solubilized in dry ILs and should be implemented for thermal stabilization of other proteins and TPs. In this direction, Slocik et al 395 investigated the polycationic nature of modified antibodies and their ability to form ion pairs for the conversion of primary Immunoglobulin G antibodies into stable protein liquids that retained more than 60% binding activity after repeated heating up to 125 °C. The IgG cantonized with 1-ethyl-3-(3-dimethyl aminopropyl) carbodiimide (C-IgG) was paired with Poly-(ethylene glycol) 4-nonyl phenyl 3-sulfopropyl ether anion (S) to form a room-temperature protein ionic liquid (P-IL).…”
Section: Poly(ionic Liquid)-protein Conjugatesmentioning
confidence: 99%
“…Many categories of polymer materials exist with a wide range of synthesis methods, most of which involve conditions that are harsh for biological systems due to high temperatures, exposure to solvents, radical generation, and UV radiation. Some studies have shown the possibility of proteins surviving these conditions, whether by protecting the protein with additives or encapsulation, or engineering the enzyme to be more robust. While promising, these approaches limit the biological function to a single enzyme or a set of enzymes without programmable dynamic response and require reengineering the formulation or protein sequence variant for each new application.…”
Section: Introductionmentioning
confidence: 99%